FAKTOR YANG BERHUBUNGAN DENGAN PROSES PERAWATAN KESEMBUHAN KLIEN HARGA DIRI RENDAH DI RUMAH SAKIT KHUSUS DAERAH PROVINSI SULAWESI SELATAN - Lorantina A (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
Objective: The purpose of this study was to look at factors related to the healing process of low self-esteem clients at the Special Hospital of South Sulawesi Province. Method: In this study used the research design used in this study is cross sectional that researchers do observation or measurement of variables at one time. The sample size in this study are 32 respondents who match the inclusion criteria. The data were collected by using questionnaires. Results: The results showed that there was a relationship between the implementation strategy and the low self-esteem healing process (p = 0,000), and there was a relationship between family support and the low self-esteem healing process (p = 0.050). Conclusion: The conclusion in this research is there is a relationship between implementation strategy and family support with the process of low self-esteem cure. Suggestion: Sarannya result of this research can be used as input for nurse about effectiveness strategy of communication implementation to cognitive and psychomotor ability of patient of low self esteem in increase self-esteem